Patterns of Orofacial Clefting in New York City From 1983 to 2010: Trends by Racial Background, Birthplace, and Public Health Strategies. (October 2018) - Butts, Sydney C.; Reynolds, Simone; Gitman, Lyuba; Patel, Prayag; Joseph, Michael
Objective: To determine the role of racial background, public health initiatives, and residence on the prevalence of orofacial clefts (OFCs) in New York City (NYC). Design/Methods: Retrospective review of OFC cases from the New York State Congenital Malformations Registry. Patients/Participants: Patients born with an OFC and all live births to mothers residing in NYC between 1983 and 2010. Main Outcome Measures: Orofacial cleft birth prevalence by cleft type, race, and borough of maternal residence for each year and by time period around the implementation of public health interventions including folate supplementation. Results: A total of 3557 cases were reviewed. The prevalence remained stable for cleft palate and cleft lip with or without cleft palate (CL ± P) in sequential time periods of the study. Among CL ± P cases, cleft lip prevalence decreased early in the study compared to increases in cleft lip and palate prevalence. For most years, the prevalence of OFCs was lower among African Americans than whites. A total of 12% to 26% of mothers in 4 of the NYC boroughs deliver outside of their borough of residence, choosing to give birth in Manhattan most often. No difference in OFC prevalence was shown in any of the 5 NYC boroughs. Conclusions: The period prevalence remained relatively stable during the time periods before and after the implementation of folate supplementation for OFCs in NYC. Prevalence of OFC subtypes was lower for most time periods during this study among African Americans compared to whites. Several factors may explain the choice of birthplace outside of the mother's borough of residence.